'Dear Mum and Dad' - Estella Cheung (Asia Pacific Network, 2001)
'By sunrise, on this bloody Tuesday, June 26, 2001, Port Moresby came under siege. Four people, including two students from the University of PNG, had been shot dead. Their bodies were driven to the Port Moresby General Hospital morgue. Seventeen protesters with pellet wounds were admitted to the hospital's emergency ward.'